PROFESSIONAL COMPETENCE OF A TEACHER - Khurshida Pulatovna Kenjaeva (Modern American Journals, 2025)
The article explores the concept of professional competence of a teacher as a critical factor in ensuring the quality and effectiveness of the educational process. It examines the core components of teacher competence, including subject-matter expertise, pedagogical and psychological knowledge, communication skills, and reflective practices. Special attention is given to the modern challenges faced by educators in the context of updated educational standards and the digital transformation of education. The article emphasizes the importance of continuous professional development and highlights key strategies for enhancing teacher competence. Findings from practical teaching experience underline the necessity of integrating theoretical knowledge with real-world teaching skills.
Keywords: Professional competence, teacher, education, teaching practice, professional development, educational standards, pedagogical skills, digital education.